2020
DOI: 10.1017/s0022215120000936
|View full text |Cite
|
Sign up to set email alerts
|

A survey of ENT undergraduate teaching in the UK

Abstract: AbstractBackgroundENT presentations are prevalent in clinical practice but feature little in undergraduate curricula. Consequently, most medical graduates are not confident managing common ENT conditions. In 2014, the first evidence-based ENT undergraduate curriculum was published to guide medical schools.Obje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…When assessing the extent to which UK medical school learning outcomes currently correlate with a suggested undergraduate curriculum provided by Student and Foundation Doctors in Otolaryngology, a survey of two medical schools found that approximately 50 per cent of suggested outcomes were met and the majority did not deliver teaching on common ENT clinical skills. 17 Examples of successful clinical skills teaching include flexible nasolaryngoscopy training with a mannequin 18 and ENT boot camps. 19…”
Section: Discussionmentioning
confidence: 99%
“…When assessing the extent to which UK medical school learning outcomes currently correlate with a suggested undergraduate curriculum provided by Student and Foundation Doctors in Otolaryngology, a survey of two medical schools found that approximately 50 per cent of suggested outcomes were met and the majority did not deliver teaching on common ENT clinical skills. 17 Examples of successful clinical skills teaching include flexible nasolaryngoscopy training with a mannequin 18 and ENT boot camps. 19…”
Section: Discussionmentioning
confidence: 99%
“…The run-through scheme increased trainer engagement and gave geographical stability to the trainees, who were well motivated from an early stage in their medical careers. This complements surveys of the attitudes and experiences towards ENT training of students and general practitioners, investigated in recent issues of The Journal , 12,13 and a more historical but seminal article in The Journal on undergraduate ENT education. 14…”
mentioning
confidence: 92%
“… 2 This has been a common occurrence in the United Kingdom with no marked improvement over the years. 3 Furthermore, this results in the majority of ENT trainees lacking formal teaching on the management of common Accident and Emergency presentations, such as epistaxis, nasal fractures, and upper aerodigestive tract obstruction from foreign body.…”
Section: Introductionmentioning
confidence: 99%